ANALISIS PENERAPAN SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA LARISPA INDONESIA - Edy Dermawan; Rizqy Fadhlina Putri; Ratna Sari Dewi (Program Studi Akuntansi Fakultas Ekonomi UMN AL Washliyah, 2023)
This study aims to analyze the system of applying cash receipts and disbursements accounting information to LARISPA. The problem raised in this study is that the accounting information application system at LARISPA Indonesia has not been effective, because the journal.id system has not been used maximally, there have been errors in inputting it, and there are still improvements in the system. the object of this research is LARISPA Indonesia. This research is a qualitative research and uses descriptive analysis. The data analysis method is by collecting, analyzing data in applying the accounting information system at LARISPA Indonesia. The results showed that a good accounting information system has played a role in improving the cash receipts internal control system. This can be seen from the cash receipts accounting information system, which is an online system that works with third parties. So that with this accounting information system it can guarantee cash security implemented by LARISPA Indonesia so that it plays an important role in improving the internal control system in terms of providing and providing accurate and reliable information on cash receipts